QUESTIONS OF IMPROVEMENT OF ASSESSMENT AND ACCOUNTING EQUIPMENT FOR INSTALLATION - Rozikov Jalil Jalolovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article reveals the features of accounting for the movement and evaluation of equipment for installation. It would be wrong to directly recognize the costs of acquiring equipment as a capital investment, since not all of them can be directed to capital investments. Some of the equipment can be sold, some of them are used for the purposes of core business activities. One of the main issues of accounting for equipment for installation is the methodology for their evaluation. Accounting for the formation of stocks of equipment for installation - domestic and imported and the methodology for determining their cost differ from each other. The reason for this is the diversity of conditions and ways of forming their stocks. As a consequence, the composition of procurement costs of their formation are also distinguishable from each other, which directly affects the criteria for their evaluation. The article provides algorithms for assessing equipment for installation - domestic and imported production, as well as the procedure for their accounting: - formation of stocks; transfer to installation; write-offs in capital investments; sale and disposal for a number of other reasons from the balance sheet of the enterprise.